2008
DOI: 10.1080/10428190701661508
|View full text |Cite
|
Sign up to set email alerts
|

Purposiveness, physical activity, and perceived health in cardiac patients

Abstract: The present results underscore the importance in cardiac rehabilitation of the continued study of factors that foster meaning in life, including a sense of purpose and individual growth, and of their potential to promote recovery of cardiac patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 32 publications
6
38
1
1
Order By: Relevance
“…Because meaning is central to humans' health and well-being (King et al, 2006;Schulenberg et al, 2008;Wong & Fry, 1998), serving as a mediating variable (Chan, 2009;Halama & Dedova, 2007;Ho et al, 2010;Holahan et al, 2008;Kleftaras & Psarra, 2012), meaning has become one of the core facets of the positive psychology movement as well as in the health promotion field. This study's PIL mean score was 93.09 (SD 5 14.85), which is in accordance with previous research (Bondevik & Skogstad, 2000).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because meaning is central to humans' health and well-being (King et al, 2006;Schulenberg et al, 2008;Wong & Fry, 1998), serving as a mediating variable (Chan, 2009;Halama & Dedova, 2007;Ho et al, 2010;Holahan et al, 2008;Kleftaras & Psarra, 2012), meaning has become one of the core facets of the positive psychology movement as well as in the health promotion field. This study's PIL mean score was 93.09 (SD 5 14.85), which is in accordance with previous research (Bondevik & Skogstad, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…In general, meaning has been found to be a strong individual predictor of life satisfaction (Morgan & Farsides, 2009;Peterson, Park, & Seligman, 2005;Seligman 2002) and an important psychological variable that promotes well-being (Bonebright, Clay, & Ankenmann, 2000;Fry, 2001;Melton & Schulenberg, 2008) and protects individuals from negative outcomes (Haugan Hovdenes, 2002;Pearson & Sheffield, 1989). Meaning seems to serve as a mediating variable in psychological health (Chan, 2009;Halama & Dedova, 2007;Ho, Cheung, & Cheung, 2010;Holahan, Holahan, & Suzuki, 2008;Kleftaras & Psarra, 2012).…”
mentioning
confidence: 94%
“…According to relevant studies, PIL demonstrates a good reliability and validity according to split-half (.87 -.92) and test-retest method (.79 -.83) (Crumbaugh, 1968;Crumbaugh & Maholick, 1964;Meier & Edwards, 1974;Reker & Cousins, 1979). PIL has also significant correlations with psychological health, well-being and social attitudes (Chan, 2009;Halama & Dedova, 2007;Ho et al, 2010;Holahan et al, 2008;Lethborg et al, 2007;Jaarsma et al, 2007;Visser et al, 2010). Regarding the factorial analysis of PIL test, some studies have concluded that PIL test is a uni-dimensional scale (Garfield, 1973;Zeitchik, 2001), while others have found that the questionnaire contains more than one dimensions (Chamberlain & Zika, 1988;Harlow, Newcomb, & Bentler, 1986;Shek, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…In general, meaning of life has been positively associated with physical/psychological health/well-being and psychopathology and seems to serve as a mediator factor in psychologycal health (Chan, 2009;Fox & Leung, 2009;Halama & Dedova, 2007;Ho, Cheung, & Cheung, 2010;Holahan, Holahan, & Suzuki, 2008;Owens, Steger, Whitesell, & Herrera, 2009) and death acceptance/fear of death (Routledge & Juhl, 2010;Thompson, Noone, & Guarino, 2003). Additionally, people who can find meaning in negative experiences, such as cancer (Jaarsma, Pool, Ranchor, & Sanderman, 2007;Lethborg, Aranda, Cox, & Kissane, 2007;Visser, Garssen, & Vingerhoets, 2010), HIV (Lyon, 1997;Lyon & Younger, 2001) or the loss of a child (Coyle, 1998), seem, after the incident, to cope better with the situation, in comparison to those that cannot find meaning.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that individuals with higher levels of purpose in life tend to engage in more healthy behaviors. For example, studies have shown that people with more purpose in life are more likely to exercise, participate in preventative behaviors, such as doctor visits, and seek out adequate relaxation (Holahan et al 2008;Kim et al 2014;Holahan et al 2011). It is possible that engagement in these types of healthy behaviors by the individuals who are high in purpose in life could lead to reduced risk of developing sleep apnea and RLS symptoms.…”
Section: Discussionmentioning
confidence: 99%